AB0499 The Influence on Hepatitis B Virus Infection in Rheumatoid Arthritis Patients Undergoing Treatment with Newer Dmard, Iguratimod. (9th June 2015) - Li, Y.-H.; Mo, Y.-Q.; Wei, X.-N.; Yang, L.-J.; Dai, L.
Abstract : Background: The hepatitis B surface antigen (HBsAg) carrying rate of rheumatoid arthritis (RA) was 11.2% in China according to recent studies. HBV infection is a major issue in RA patients undergoing disease-modifying anti-rheumatic drugs (DMARDs) therapy. Iguratimod was a newer effective conventional DMARD, which was small molecular and approved in China in Augest, 2011. However, little was known about the influence of iguratimod to liver injury and HBV reactivation. Objectives: To explore the influence of iguratimod on HBV reactivation in HBsAg/HBcAb+ RA patients and the influence on HBsAb titer in HBsAb+ RA patients. Methods: Patients with active RA were enrolled from October 2013 to September 2014. All were treated with iguratimod (25mg Bid) alone or in combination with other conventional DMARDs for 24 weeks, such as methotrexate (MTX), leflunomide (LEF), etc. Adding with non-steroidal anti-inflammatory drugs (NSAIDs) or small doses of corticosteroids was permitted if constant pain observed. HBsAg+ RA patients were suggested to be treated with anti-virus therapy preventively. Liver function, HBsAg or HBsAb titer, and HBV-DNA load were evaluated at baseline, 12th and 24th week. HBV reactivation was defined as a 10-fold rise in HBV-DNA compared to baseline or HBsAg/HBeAg switch from undetectable to detectable. Results: 1) Thirty-six patients with active RA were enrolled and 74% (29/36) were female, age (median and IQR, similarly hereinafter) was 49 (39–58) years, disease duration was 59 (23–81) months, and DAS28-CRP was 4.44 (3.96–5.75). Twelve patients received iguratimod monotherapy. 2) Patients with active RA were grouped according to serum HBV biomarkers, including chronic or past HBV infection group (HBsAg or HBcAb +, N=20) and free of HBV infection group (HBsAg and HBcAb -, N=16).There was no significance difference of transaminases (AST 18 (14–24) vs 17 (12–25), ALT 14 (12–30) vs 13 (8–22)) and DAS28 (4.82 (4.03–5.85) vs 4.28 (3.81–5.65)) of baseline (all P>0.05). 3) The chronic or past HBV infection group was divided into chronic HBV infection subgroup (HBsAg or HBV-DNA +, n=3) and past HBV exposed subgroup (HBcAb + but HBsAg-, n=17). In the chronic HBV infection subgroup, all refused antiviral prophylaxis, and 2 developed HBV reactivation without aminotransferases elevation in 10th and 24th weeks. In pass HBV exposed subgroup, 2 patients developed transient 3-times elevation of aminotransferases in 24th weeks. 4) In free of HBV infection group, none developed transaminases elevation. The changes of HBsAg and HBsAb has no statistical significance among baseline, 12th and 24th weeks according to repeated measures analysis of variance ( F =0.795, P =0.472) and Wilcoxon Matched-Pairs Signed-Ranks Test (all P >0.05). Conclusions: Active RA patients should be screened for liver function and HBV biomarker before iguratimod therapy. RA patients with HBV infection, especially with positive baseline HBV-DNA, were recommended to be treated with antiviral prophylaxis and monitor liver function and HBV-DNA load regularly. Acknowledgements: This work was supported by National Natural Science Foundation of China (grant no. 81471597), Specialized Research Fund for the Doctoral Program of Higher Education (grant no.20130171110075) and Guangdong Natural Science Foundation (grant no.S2013010014396). Disclosure of Interest: None declared